EXPLORATION OF COMMUNITY NURSES’ KNOWLEDGE AND INTEREST AGAINST THE PROMOTIONAL TRAINING OF CONTINUOUS AMBULATORY PERITONEAL DIALYSIS: AN EXPERIMENTAL STUDY - Ridha Afzal; Yuly Peristiowati; Agustin Widyowati (International Journal of Medical Science and Public Health Research, 2024)
Background: The rise of the CAPD program over the last two years has left a problem where the role of community nurses in health promotion activities related to the implementation of the Continuous Ambulatory Peritoneal Dialysis (CAPD) program in the community has not been specifically transparent, especially about their knowledge and interests. Concrete exploration is needed regarding the knowledge and interests of those community nurses. Objectives: to obtain post-CAPD training evaluation results regarding community nurses' knowledge and interest in the CAPD promotional activities. Methods: This research used quantitative methods with an experimental design. The population was 100 nurses. The sampling technique was purposive sampling. The instruments used were pre and post-test questions about knowledge in Multiple Choice Questions (MCQ). The independent variables were the knowledge and interest of community nurses. The dependent variable is CAPD training. This research design was divided into two groups, namely the first group was an experimental group that was given CAPD training and the second group was a control group without CAPD training. Data were processed using SPSS and analyzed comparatively and quantitatively using the Paired Sample T-Test. Results: The level of knowledge of community nurses in the group without treatment was in the poor category (56.0%), and their level of interest was in the low category (64.0%). The level of knowledge of community nurses in the pre-training group is in the low category (54.0%), and the level of interest is in the high category (52.0%). the level of knowledge of post-training community nurses is in the good category (80.0%), and the level of interest is in the high category (74.0%). The study results show p-values 0.035 and 0.019, meaning < 0.05, so Ha is accepted. Conclusion: In conclusion, there is a significant difference between the averages of the pre-test and the post-test scores regarding community nurses' participation in CAPD promotion after being given training.